CdS core-Au plasmonic satellites nanostructure enhanced photocatalytic hydrogen evolution reaction. (July 2018) - Xu, Juan; Yang, Wei-Min; Huang, Shi-Jie; Yin, Hao; Zhang, Hua; Radjenovic, Petar; Yang, Zhi-Lin; Tian, Zhong-Qun; Li, Jian-Feng
Abstract: Photocatalytic hydrogen production from water splitting is a renewable non-polluting method for converting abundant solar energy to a useable fuel and has gained considerable interest recently. However, energy conversion efficiencies remain low and need to be improved if solar generated hydrogen fuel is to be a reality. Here, we have developed a highly active CdS core-Au plasmonic satellites nanostructure composite catalyst, which efficiently facilitates the hydrogen production from water reduction under visible light. Compared to pure CdS, such catalysts exhibited over 400 times higher photocatalytic activity due to the surface plasmon resonance (SPR) effect of the Au satellites. Furthermore, their activities are strongly dependent on the particle size of the Au satellites, and an extremely high photocatalytic hydrogen production rate of 6385 μmol g −1 h −1 was achieved using CdS-16 nm Au under visible-light irradiation. The enhancement mechanism for the CdS core-Au plasmonic satellites catalyst has also been studied comprehensively by tailoring the structure of the catalysts and reaction conditions. A synergistic effect combining both near-field enhancement and "hot" electron transfer has been uncovered and accounts for the great enhancement. This work well demonstrates that the SPR enhancement can greatly boost the photocatalytic activity of traditional semiconductor photocatalysts, thus provides a promising strategy to develop highly efficient photocatalysts for solar energy conversion. Graphical abstract: A CdS core-Au plasmonic satellites nanostructure catalyst with excellent photocatalytic activity for hydrogen production was developed and the SPR enhancement mechanism was systematically studied.fx1 Highlights: A CdS core-Au satellites plasmonic photocatalyst is developed for SPR-enhanced photocatalytic hydrogen production. The photocatalytic activity of the plasmonic catalyst is enhanced by over 400 times. The synergetic effect between near-field enhancement and "hot" electron transfer mechanism are demonstrated. Light absorption spectral overlap between the semiconductor and plasmonic material is necessary for effective SPR enhancement.